11. Music and Engineering - A New Paradigm of Arts and Engineering Education - Stanciu Mariana Domnica; Nauncef Alina Maria; Crețu Constantin Nicolae; Câmpean Mihaela; Roșca Ioan Călin; Dinulică Florin; Cerbu Camelia; Mihălcică Mircea; Gliga Vasile Ghiorghe; Savin Adriana; Nastac Silviu Marian (Sciendo, 2022)
The paper presents the interdisciplinary approach of two fields - the artistic (musical) and technical (forestry engineering, wood processing engineering, mechanical and physical engineering) apparently opposite but which can be happily exploited for both parties. Thus, we can speak of a new paradigm of education through which art can combine with the technical sciences for the benefit of all. The aim of the paper is to present experimental methods in mechanical and acoustic evaluation of violins from engineering and artistic perspectives. The presented results are part of a larger study carried out within an experimental demonstration research project.